Analisis Struktur, Perilaku dan Kinerja Industri Kreatif di Indonesia - Siti Munawaroh (Epistemik: Indonesian Journal of Social and Political Science, 2020)
The purpose of this study is to analyze structure, conduct and performance of creative industry in Indonesia with an annual 2005-2015 and data totaled 6 subsector in creative industry in group ISIC code 2 digit. The type data at this research in secondary data which is collection from Badan Pusat Statistik (BPS) and literature related to this study. The method use Structure-ConductPerformance (SCP) analysis and panel data analysis with Random Effect Model (REM). The result of SCP analysis found that the industrial structure of creative industry in Indonesia is an oligopoly structure, with an average value of MS of 55 percent and CR2 of 49 percent. Analysis of conduct of industry seen strategy of product, price and promotion. In terms of performance can be seen from PCM and Efficiency. The estimation result of panel data indicated that by parsial, variable that have the greatest effect and significant performance increased Efficiency is Market Share and variable no significant performance decrease Efficiency is CR2 of creative industry in Indonesia. And by simultan, MS and CR2 have effect on Efficiency.